LEGAL PROTECTION FOR VICTIMS OF "SILENT RAPE IN MARRIAGE" BASED ON A VICTIMOLOGY PERSPECTIVE - Rizki Hagina Sinulingga; Dinda Dinanti (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Sexual violence within marriage that goes unreported commonly referred to as silent rape in marriage constitutes one of the most concealed forms of human rights violation in Indonesian domestic life. This study aims to analyze the legal protection available to victims of silent rape in marriage from a victimological perspective, while identifying the normative and structural barriers that impede effective protection. The research employs a normative juridical method combining a statute approach and a case approach, supported by qualitative descriptive analysis. The findings reveal that Indonesian positive law has progressively constructed a protective framework through Law No. 23 of 2004 on the Elimination of Domestic Violence (UU PKDRT), Law no. 12 of 2022 on Sexual Violence Crimes (UU TPKS), and the New Penal Code under Law No. 1 of 2023, which collectively forms a legal safety net for victims. However, from a victimological standpoint, legislative reform alone is insufficient, as victims continue to face layered obstacles including a pervasive culture of victim blaming, social stigma, economic dependence on perpetrators, and a lack of gender-sensitive law enforcement conditions that give rise to the phenomenon of double victimization. This study concludes that the true measure of victim protection lies not in the sophistication of legal texts, but in the extent to which victims genuinely experience the benefits of that protection in their daily lives. Accordingly, regulatory harmonization, transformation of law enforcement paradigms, expansion of integrated victim services, and sustained anti-victim blaming campaigns are essential as a unified strategy for addressing silent rape in marriage in Indonesia.